Deep insight into the ash fusibility and viscosity fluctuation behavior during co-gasification of coal and indirect coal liquefaction residue. (1st December 2021) - Zhang, Linmin; Wei, Juntao; Wang, Jiaofei; Bai, Yonghui; Song, Xudong; Su, Weiguang; Lv, Peng; Nai, Guoxing; Yu, Guangsuo
Highlights: Effect of ICLR addition on ash fusibility and viscosity of YCW coal were studied. "Barbed-shape" needle-like crystal was the main cause of viscosity fluctuation. ICLR additive inhibited the increase of crystal aspect ratio and volume fraction. The addition of ICLR alleviated the viscosity fluctuation behavior of YCW coal ash. Abstract: Co-gasification of coal and indirect coal liquefaction residue (ICLR) is an effective approach to large-scale utilization of ICLR. In this work, the effect of ICLR addition on ash fusion characteristics and viscosity-temperature characteristics of YCW coal were studied by means of ash fusion temperature analyzer (AFTA), XRD, high-temperature-rotary-viscometer, high-temperature heating stage coupled with optical microscope (HTSOM) and FactSage thermodynamics software. The results showed that with the increase of ICLR mass fraction, the low-temperature eutectic anorthite melted into a liquid phase, resulting in a linear decrease of AFTs. Moreover, the causes of viscosity fluctuation were revealed according to the in-situ crystallization morphology variation and viscosity-temperature characteristic curves. It was found that the formation of a large number of "barbed-shape" needle-like crystals during the cooling process was the main reason for the significant viscosity fluctuation. With the addition of ICLR, the length-diameter ratio and volume fraction of the "barbed-shape" needle-like crystals decreased significantly, resulting in the decrease of viscosity fluctuation. When the addition amount of ICLR was 3%, the "barbed-shape" needle-like crystals were not precipitated during the entire crystallization process, and the viscosity no longer fluctuated. As the mass fraction of ICLR increased to 5%, no crystals precipitation was observed in the cooling process. At this time, the slag sample showed the glass slag characteristics. Therefore, for entrained-flow gasification, the addition of ICLR could improve the gasification efficiency by reducing the gasifier operating temperature, and avoid slag-tapping problems by alleviating the viscosity fluctuation. More importantly, it could realize the resource treatment of hazardous waste and transform hazardous waste into solid waste.